Recent advances in the diagnosis of COVID-19: a bird’s eye view - Sharma, Bhawna (Expert Rev Mol Diagn, 2021)
INTRODUCTION: The COVID-19 pandemic is still escalating and has shaped an extraordinary and pressing need for rapid diagnostics with high sensitivity and specificity. Prompt diagnosis is the key to mitigate this situation. As several diagnostic tools for COVID-19 are already available and others are still under development, mandating a comprehensive review of the efficacy of existing tools and evaluate the potential of others. AREAS COVERED: Currently explored platforms for SARS-CoV-2 diagnostics and surveillance centered on qRT-PCR, RT-PCR, CRISPR, microarray, LAMP, lateral flow immunoassays, proteomics-based approaches, and radiological scans are overviewed and summarized in this review along with their advantages and downsides. A narrative literature review was carried out by accessing the freely available online databases to encapsulate the developments in medical diagnostics. EXPERT OPINION: An ideal detection method should be sensitive, specific, rapid, cost-effective, and should allow early diagnosis of the infection as near as possible to the point of care that could alter the current situation for the better. Medical diagnostics is a highly dynamic field as no diagnostic method available for SARS-CoV-2 detection offers a perfect solution and requires more attention and continuous R&D to challenge the present-day pandemic situation